MDR carbapenemase-producing Klebsiella pneumoniae of the hypervirulence-associated ST23 clone in Poland, 2009–19. (30th September 2022) - Biedrzycka, M; Izdebski, R; Urbanowicz, P; Polańska, M; Hryniewicz, W; Gniadkowski, M; Literacka, E
Abstract: Objectives: To characterize carbapenemase-producing isolates of the Klebsiella pneumoniae hypervirulent (hvKp) clone ST23 in Poland. Methods: Fifteen K. pneumoniae ST23 isolates were identified by the Polish surveillance of carbapenemase-producing Enterobacterales. These comprised a cluster with KPC-2 + NDM-1 ( n  = 7), KPC-2 ( n  = 1) or NDM-1 ( n  = 1) enzymes from one hospital from 2018, and sporadic isolates with KPC-2 ( n  = 1), NDM-1 ( n  = 1), VIM-1 ( n  = 1) or OXA-48 ( n  = 3), recovered from 2009 to 2019 in different towns. The isolates were sequenced by Illumina MiSeq, followed by MinION for six representatives. Clonality, phylogeny, serotypes, virulomes, resistomes and plasmids of the isolates were analysed and compared with international ST23 strains, using various bioinformatic tools. Results: Only two diverse isolates with KPC-2 or VIM-1 were of typical hvKp ST23 serotypes K1 and O1v.2, and its predominant phylogenetic clade. These contained multiple chromosomal ( ybt, clb ) and pK2044/KpVP-1 plasmid ( iuc, iro, rmpADC, rmpA2 ) virulence loci, whereas carbapenemase and other antimicrobial resistance (AMR) genes were on single additional plasmids. All remaining isolates were of K57 and O2v.2 serotypes, and a minor, distant clade of unclear phylogeny, including also ∼10 isolates from other European countries. These had fewer virulence loci ( ybt, iuc, rmpADC, rmpA2 ) but abounded in plasmids, which with several chromosomal AMR mutations conferred more extensive MDR phenotypes than in K1 O1v.2. Lower clonal diversity than in K1, and numerous common characteristics of the isolates supported the hypothesis of the emerging character of the ST23 K57 clade. Conclusions: A new MDR ST23 lineage has emerged in Europe, causing a potential threat to public health.